2014
DOI: 10.1080/19440049.2014.972472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the bread-making process on zearalenone levels

Abstract: The effects of the bread-making process including fermentation with Saccharomyces cerevisiae and lactic acid bacteria (Lactobacillus casei, Lactobacillus rhamnosus, Lactobacillus acidophilus and Lactobacillus fermentum) and baking at 200°C on zearalenone (ZEA) levels were investigated. Standard solutions of ZEA were added to flour and then loaves of bread were prepared. Sourdough and three types of yeast including active dry yeast, instant dry yeast and compressed yeast were used for the fermentation of dough.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…() was found to be reduced during yeast fermentation by around 30% to 34%. The bread dough was prepared using spiked flour with OTA levels of 2, 5, and 10 μg/kg and fermented at around 30 °C for 1 h. Milani and Heidari () found, similar to a study on ZON (Heidari et al., ), different effects by different types of baker's yeast and of lactobacilli fermentation on OTA. The most pronounced reduction of OTA in flour spiked to a level of around 0.2 μg/kg was caused by compressed yeast (around 63% OTA loss in total).…”
Section: Effects Of Food Processing On Mycotoxin Levels In Wheat and mentioning
confidence: 82%
See 2 more Smart Citations
“…() was found to be reduced during yeast fermentation by around 30% to 34%. The bread dough was prepared using spiked flour with OTA levels of 2, 5, and 10 μg/kg and fermented at around 30 °C for 1 h. Milani and Heidari () found, similar to a study on ZON (Heidari et al., ), different effects by different types of baker's yeast and of lactobacilli fermentation on OTA. The most pronounced reduction of OTA in flour spiked to a level of around 0.2 μg/kg was caused by compressed yeast (around 63% OTA loss in total).…”
Section: Effects Of Food Processing On Mycotoxin Levels In Wheat and mentioning
confidence: 82%
“…(), ZON was not changed during wheat bread dough preparation and fermentation. In contrast, Heidari, Milani, and Nazari () detected lower ZON levels after fermentation. They found different effects from different types of baker's yeast and of lactobacilli fermentation on the reduction of ZON as follows: compressed yeast > sourdough > active dry yeast > instant dry yeast.…”
Section: Effects Of Food Processing On Mycotoxin Levels In Wheat and mentioning
confidence: 86%
See 1 more Smart Citation
“…Considering these results, compressed yeast compared to other yeasts showed the most destructive effect, in previous study, compressed yeast was shown similar result (Heidari et al . ). This ability can be correlated to higher CO2 production, leading to a decrease in pH and formation of various fermentation metabolites such as acids and alcohols, which caused higher destruction of OTA by compressed yeast.…”
Section: Discussionmentioning
confidence: 97%
“…Then, 1.0 ml diluted solution which had 125 ng mycotoxin was sprayed to 25.0 g of rice sample at ambient temperature. After evaporation of the solvent, the sample was stirred to provide a good distribution of OTA in the rice (Heidari, Milani, & Nazari, 2014). …”
Section: Methodsmentioning
confidence: 99%